2013
DOI: 10.1177/0143034313479699
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and victimization: Predictive role of individual, parental, and academic factors

Abstract: This study explored the roles of individual factors (age, gender, locus of control, selfesteem, and loneliness), parenting style, and academic achievement in discriminating students involved in bullying (as bullies, victims, and bully/victims) from those not involved. Participants comprised 742 middle school students (393 females, 349 males). The results of multinomial logistic regression analysis indicated that a higher locus of control, lower strictness/supervision scores, increased age, and being male incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 61 publications
6
50
1
11
Order By: Relevance
“…However, most of the works offer results that are consistent with the existence of a curvilinear relationship between the two variables. The probability of a student being a bully increases from grade to grade until about age 14 years, when it decreases (Atik & Güneri, 2013;Caballo et al, 2011;Carlyle & Steinman, 2007;CDC, 2011;Gendron et al, 2011;Nation et al, 2008;Volk et al, 2006;Wei et al, 2010;. However, some studies have found a progressive decrease in the probability of being a bully from age 11-12 years onwards Shetgiri, Lin, Avila, & Flores, 2012;.…”
Section: Samplementioning
confidence: 99%
See 4 more Smart Citations
“…However, most of the works offer results that are consistent with the existence of a curvilinear relationship between the two variables. The probability of a student being a bully increases from grade to grade until about age 14 years, when it decreases (Atik & Güneri, 2013;Caballo et al, 2011;Carlyle & Steinman, 2007;CDC, 2011;Gendron et al, 2011;Nation et al, 2008;Volk et al, 2006;Wei et al, 2010;. However, some studies have found a progressive decrease in the probability of being a bully from age 11-12 years onwards Shetgiri, Lin, Avila, & Flores, 2012;.…”
Section: Samplementioning
confidence: 99%
“…Narcissism would especially contribute to the stability over time of bullying perpetration. Perhaps because of this ambivalent relationship between self-esteem and being a bully, the majority of the reviewed studies analyzing the relationship between the two variables have found that the association between them is nonsignificant (Atik & Güneri, 2013;Nation et al, 2008;; that is, the probability of being a bully is independent of the students' degree of self-esteem.…”
Section: Psychological Factorsmentioning
confidence: 99%
See 3 more Smart Citations